Combined effect of sodium nitrite with high‐pressure treatments on the inactivation of Escherichia coli BW25113 and Listeria monocytogenes NCTC 11994. (7th January 2013) - De, M.; Bravo, D.; Medina, M.; Park, S.F.; Mackey, B.M.
Abstract The bactericidal effect of acidified sodium nitrite alone or when combined with high hydrostatic pressure (HHP) treatment was examined with Escherichia coli BW25113 and Listeria monocytogenes NCTC 11994. A powerful synergistic effect of HHP plus nitrite was observed at pH 4·0, but not at higher pH values. Escherichia coli hmpA and norV mutants lacking defences against nitrosative stress were more sensitive to pressure combined with acidified sodium nitrite than the wild‐type strain, suggesting an involvement of nitric oxide in the bactericidal effect. Significance and Impact of the Study High hydrostatic pressure (HHP) is an effective nonthermal food preservation technology that can be used to increase food safety and shelf life with minimal changes in food quality. Various antimicrobial agents including bacteriocins, lysozyme, chitosan, lactoperoxidase and essential oils have been tested in combination with HHP to enhance the effect of mild‐pressure treatments. This is the first report of a synergistic bactericidal effect of high pressure and acidified nitrite. A better understanding of combined preservation processes and synergistic effects will help ensure the safety of processed foods.